2y^2-7y+6= 2y^2-4y-3y+6
=2y(y-2)-3(y-2)
=(2y-3)(y-2)
Therefore
y=3/2 or y=2
Answer: 3.2 miles
Step-by-step explanation: Trust me bro. 1000% right
The answer is A. To understand that, you need to put it in order by the x's and the y's to get x^2-6x + y^2-16y = -48. Now complete the square on both the x and the y terms to get (x^2-6x+9) +(y^2-16y+64) = -48+9+64. Rewriting that in vertex form on the left and doing the math on the right gives you
(x-3)^2 + (y-8)^2 = 25, which shows you a center of (3,8) and a radius of 5.
Answer:
let sum of money be x
amount=rupees5454
rate=8%
time=30 months
convert month into year
30/12=5/2 years
Step-by-step explanation:
interest=p*t*r/100
=x*5*8/100*2
=40x/200
=x/5
so to find principal use formula
amount=principal +interest
5454=x+x/5
5454=5x+x/5
5454*5=6x
27270/6=x
4545=x
therefore ,sum of money(principal)=rupees.4545
Hope this helps u!!
Personally I'd solve this inequality for y first: y < x-3.
That immediately eliminates (6,2) and (2,6).
Starting from y < x-3 and letting 2 sub for x and -1 sub for y, is the following true or false?
-1 < 2 -3 NO. -1 < -1 is false. Was there a fourth answer choice?